Development of a theory-informed questionnaire to assess the acceptability of healthcare interventions - Sekhon, Mandeep; Cartwright, Martin; Francis, Jill J. (BMC health services research, 2022)
Background The theoretical framework of acceptability (TFA) was developed in response to recommendations that acceptability should be assessed in the design, evaluation and implementation phases of healthcare interventions. The TFA consists of seven component constructs (affective attitude, burden, ethicality, intervention coherence, opportunity costs, perceived effectiveness, and self-efficacy) that can help to identify characteristics of interventions that may be improved. The aim of this study was to develop a generic TFA questionnaire that can be adapted to assess acceptability of any healthcare intervention. Methods Two intervention-specific acceptability questionnaires based on the TFA were developed using a 5-step pre-validation method for developing patient-reported outcome instruments: 1) item generation; 2) item de-duplication; 3) item reduction and creation; 4) assessment of discriminant content validity against a pre-specified framework (TFA); 5) feedback from key stakeholders. Next, a generic TFA-based questionnaire was developed and applied to assess prospective and retrospective acceptability of the COVID-19 vaccine. A think-aloud method was employed with two samples: 10 participants who self-reported intention to have the COVID-19 vaccine, and 10 participants who self-reported receiving a first dose of the vaccine. Results 1) The item pool contained 138 items, identified from primary papers included in an overview of reviews. 2) There were no duplicate items. 3) 107 items were discarded; 35 new items were created to maximise coverage of the seven TFA constructs. 4) 33 items met criteria for discriminant content validity and were reduced to two intervention-specific acceptability questionnaires, each with eight items. 5) Feedback from key stakeholders resulted in refinement of item wording, which was then adapted to develop a generic TFA-based questionnaire. For prospective and retrospective versions of the questionnaire, no participants identified problems with understanding and answering items reflecting four TFA constructs: affective attitude, burden, perceived effectiveness, opportunity costs. Some participants encountered problems with items reflecting three constructs: ethicality, intervention coherence, self-efficacy. Conclusions A generic questionnaire for assessing intervention acceptability from the perspectives of intervention recipients was developed using methods for creating participant-reported outcome measures, informed by theory, previous research, and stakeholder input. The questionnaire provides researchers with an adaptable tool to measure acceptability across a range of healthcare interventions.